Spatial and temporal variations in near‐surface energy fluxes in an Alpine valley under synoptically undisturbed and clear‐sky conditions. (23rd March 2021) - Lehner, Manuela; Rotach, Mathias W.; Sfyri, Eleni; Obleitner, Friedrich
Abstract: Diurnal cycles of turbulent sensible and latent heat fluxes are typically closely related to the diurnal cycles of solar irradiation under synoptically undisturbed and clear‐sky conditions. In mountainous terrain, large variations can occur in the topographic and surface properties, which modify the local radiation budget and thus turbulent energy fluxes and the surface energy balance. Another characteristic of mountainous terrain is local, thermally driven circulation systems, such as the slope‐ and valley‐wind system, which can equally affect turbulent exchange. Observations of near‐surface radiative and turbulent fluxes are presented from six eddy‐covariance stations in an approximately east–west‐oriented major Alpine valley for undisturbed and clear‐sky conditions. Median diurnal cycles over the whole year are compared at the six sites and related to local terrain characteristics and the thermally driven wind systems. At a scale that is smaller than grid cells in current operational global forecast models, heat, moisture, and momentum fluxes show a large spatial variability in the magnitudes and their diurnal cycles. Lowest heat fluxes are observed on the north‐facing sidewall, where solar irradiation and thus available energy are reduced compared with the valley floor and south‐facing sidewall. Differences in the land surface characteristics further affect the partitioning of the available energy into sensible and latent heat fluxes. The median sensible heat flux reaches its daily peak already before solar noon at several sites, which appears to be related to the transition from down‐valley to up‐valley winds. In contrast to flat and homogeneous terrain, horizontal heat fluxes and lateral momentum fluxes can reach magnitudes that are similar to the magnitudes of vertical heat fluxes and longitudinal momentum fluxes, respectively. Abstract : Observations are presented from eddy‐covariance stations in an east–west‐oriented Alpine valley. Near‐surface radiative, heat, moisture, and momentum fluxes show a large spatial variability in the magnitudes and the diurnal cycles of the fluxes. Differences in solar irradiation between opposing sidewalls lead to similar differences in the magnitudes of turbulent fluxes; land surface characteristics affect the partitioning of the available energy into sensible and latent heat fluxes; and the valley wind circulation impacts the momentum fluxes and the temporal evolution of the heat flux.